The Phenomenon of Sea Fencing in PIK 2 as a Sign of Government's Indecisiveness in Maintaining National Resilience - Ahmad Rizal Roby Ananta; Devi Tri Berlian Syah; Zulfikar Erlangga (JURNAL PUSPAKA, 2025)
The phenomenon of sea fencing in Pantai Indah Kapuk 2 (PIK 2) has raised concerns regarding the government's lack of decisiveness in upholding justice, humanity, and unity, which impacts national resilience. This study aims to analyze the relationship between this issue and aspects of maritime security, social justice, and economic stability, as well as to evaluate the government's role in managing coastal areas. The research was conducted in the PIK 2 area, which is part of a controversial National Strategic Project (NSP). The research employs normative legal methods with a conceptual and statutory approach, utilizing data collection techniques such as literature reviews of legal regulations, scientific journals, and international legal documents, including UNCLOS 1982. The findings reveal that the sea fencing in PIK 2, without considering the interests of coastal communities, violates the principles of social justice, exacerbates economic disparities, and threatens national unity. The study also identifies weaknesses in government oversight regarding the implementation of relevant regulations. It concludes that the government must take firm actions to review policies, strengthen oversight, and involve communities in decision-making to ensure that coastal area development aligns with Pancasila values and the goal of preserving national integrity. Keyword: Phenomenon, Government, National Resilience